Papers - New York Meeting – February, 1929 - Corrosion of Metals in the Lehigh Valley (With Discussion) - C. E. Reinhard (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1929)
A useful accelerated weathering test should be capable of placing any series of metals quantitatively in the same order of endurance as that noted under a particular set of actual exposure conditions. The development of such a test must necessarily depend to a considerable extent upon data obtained from a wide variety of exposures. This paper offers preliminary data from exposure tests on nine metals placed in 11 locations in the Lehigh Valley, within a radius of 20 miles from Palmerton. The exposure conditions vary from a severe industrial atmosphere to a pure rural atmosphere. The data are offered as evidence of the necessity for the identification and evaluation of the variables of corrosion and as illustration of some of the variations to be considered in the development of a useful accelerated test. It is quite clear, from this evidence, that a useful accelerated test must be versatile to the extent of showing the probable variations of corrosion resulting from differences in atmosphere as well as from differences in the metals. The paper is presented solely with the object of pointing out the wide variations in relative merits of several common metals in resisting corrosion and without any thought of initiating controversy regarding the merits of particular metals. For this reason the metals are designated only by symbols in the tables and no key is given to these symbols. Test Procedure Specimens, 4 by 6 in., were cut to accurate dimensions from each of the following metals or alloys: aluminum, ascoloy, copper, copper steel, galvanized iron, and zinc. Additional grades of these metals bring the total to nine types. Since it was impossible to obtain the required number of copper-steel specimens having equal surface conditions of rust and scale, it was thought advisable to pickle these specimens in a hot solution of 10 per cent. sulfuric acid. All other specimens were carefully cleaned in ether and alcohol and weighed just prior to exposure. Four specimens of each type of metal were mounted on a test rack by means of porcelain insulators. The racks were so constructed that